Newlyweds’ Perspectives in Jeddah Towards a Prevention Program Based on the Concept of Differentiation of Self - Alshomrani, Musleha Ali; Bugis, Yosra Mohammed (Journal of Humanities & Social Sciences, 2025)
The aim of the study was to apply a preventive program based on the concept of self-differentiation to a sample of newlyweds, and to reveal their views towards the program. The number of participants was (6) individuals whose ages ranged between (20-35) years, and the spouses participated together. To achieve the objectives of the study, the preventive program was designed based on the ADDIE model, and the number of it’s sessions was: (6) training sessions, (2) hours per session, implemented over (3) weeks. The study adopted the qualitative approach with a basic design, and the data were collected using a semi-standardized interview tool, and were analyzed qualitatively using the Thematic analysis method. The study reached the following results: The participation of both spouses in the program contributed to strengthening their common interests; which was positively reflected on their marital relationship, in addition to their achievement of a number of cognitive and skill outcomes that led to positive results for them; Among them: The spouses application of the systems thinking method enabled them to identify their role in the occurrence of marital problems, and by practicing stress reduction methods and self-reflection, they were able to manage stress and control emotions. All participants also presented a set of proposals for the development of the program. The study recommended the following: involving the spouses together in all marital relations programs, educating newlyweds about the importance of stress management and controlling emotions, conducting more studies on the concept of self-differentiation to reveal its role in improving aspects of the marital relationship, and creating media content targeting the family and focusing on topics including: stress management, distinguishing between feelings and thoughts and their impact on behavior, in addition to highlighting the impact of these topics on marital relations.